Mésothéliome malin de l´ovaire: à propos d´un cas - Ouafki, Imane (Pan Afr Med J, 2021)
Primary malignant mesothelioma of the ovary (PMMO) is an extremely rare tumor which can develop from mesothelial cells. This neoplasia is caused predominantly by exposure to asbestos or other cancer-causing agents. Preoperative assessment, based on computed tomography (CT) scan, magnetic resonance imaging and positron emission tomography, is essential for cancer staging. Anatomopathological diagnosis is based on immunohistochemical findings. PMMO is an exceptional disease involving a multidisciplinary therapeutic strategy including the use of chemotherapy which improves the management and prognosis of patients. This study reports the case of a female patient undergoing suboptimal surgery complemented by adjuvant chemotherapy with complete radiological response and 1-year disease-free survival.